Impact of Ejection Fraction on Health-Related Quality of Life Sub-Scales in Heart Failure Patients: A Comparative Analysis - Rokiea Abdlgader, (AlQalam Journal of Medical and Applied Sciences, 2025)
The primary goal of this study is to identify any associations between ejection fraction and several components of HRQOL, including mental, social, and physical well-being. The study evaluated patients' quality of life (QOL) in ambulatory heart failure clinics as a component of a quality improvement intervention. We assessed the effect of heart failure on patients' quality of life using the Minnesota Living with Heart Failure Questionnaire (MLHFQ). Subjects provided their informed consent and completed questionnaires that measured quality of life and family support as part of the research. There are no statistically significant differences between patients with EF ≤ 40% and those with EF > 40% across all variables measured. Patients with EF ≤ 40% had significantly worse scores in all HRQOL subscales (Physical, emotional, and other) compared to those with EF > 40%. The higher scores in the EF ≤ 40% group suggest worse quality of life in physical, emotional, and other aspects. The study reveals a link between lower ejection fraction (EF ≤ 40%) and poorer HRQOL, which points to the importance of targeted interventions and comprehensive care approaches to improve HRQOL outcomes.